Cloud Computing Adoption Trends: A Systematic Literature Review of Organizational Perspectives - Azizah, Nabila Nur (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2024)
This research presents a systematic review of cloud computing adoption trends from an organizational perspective. Leveraging a rigorous research methodology, we collect and analyze related literature studies to identify common patterns in organizations' adoption of cloud computing. The theoretical foundation covers the basic concepts of cloud computing and organizational technology adoption models, providing a framework for understanding these changes. Through an in-depth review, we uncover common trends in cloud computing adoption, such as the evolution of business models and attention to security and compliance aspects. Organizational factors, such as organizational structure and culture, play an essential role in the decision-making process regarding adopting these technologies. In addition, we explore the benefits and challenges that organizations face during the adoption process. The research also includes case studies or examples of successful cloud computing deployments, providing in-depth insights into how specific organizations overcame challenges and leveraged the benefits of the cloud. The findings pave the way for further discussion regarding practical implications for business stakeholders and future research directions. By investigating these essential elements, this research provides a comprehensive overview of cloud computing adoption trends and contributes to understanding how organizations can manage the transition to an ever-evolving technological environment.